Falls of elderly people living in rural areas: prevalence and associated factors - Fernanda dos Santos; Celmira Lange; Patrícia Mirapalheta Pereira de Llano; Marcos Aurélio Matos Lemões; Carla Alberici Pastore; Lisiane Manganelli Girardi Paskulin; Arlete Eli Kunz da Costa; José Luiz Pozo Raymundo (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to identify the prevalence and factors associated with falls in the elderly population living in rural areas. Method: this is a cross-sectional study, carried out in 2014, with 820 older adults recorded in the Family Health Strategy (Estratégia Saúde da Família). The association between the reporting of falls in 12 months and their associated factors was verified by the Chi-square and Fischer's exact tests and by multivariate logistic regression analysis. Results: the majority of the sample was female (56.1%), white (90.2%) and aged 60-69 years (54.9%). The prevalence of falls was 27.9%, and being female, hypertensive and diabetic was associated to falls. Conclusion: it is the responsibility of health professionals to have a closer look at the elderly who have these chronic diseases, especially within the scope of the Family Health Strategy, which works longitudinally with these patients, in addition to improving nursing care aimed at this population.